Hubungan Antara Dukungan Orang Tua Dan Pengetahuan Siswi Dengan Kesiapan Siswi Dalam Menghadapi Menstruasi Di MI Sanggrong Tegalrejo Purwantoro Wonogiri - Rahmawati Rahmawati; Murwati Murwati; Henik Istikhomah (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Support Parent, Knowledge Of Student, Readiness Of Student, Menstruation. Menarche is a sign of early entry of a woman in the reproductive period.Menarche is the first menstrual period experienced by all women, especially adolescents. All teenagers who will experience the first menstruation most say fear,anxiety, and not yet avail, this is due to lack of parental support and lack of knowledge of girls about menstruation so that the impact on the readiness of female students in menstrual period. Purpose: to know the relationship between parental support and knowledge students about menstruation with the readiness of students in the face of menstruation. Method: This research is a descriptive analytic research with cross sectional approach. The population in this study were all students of MI Sanggrong class IV, V, VI in 2017 which amounted to 64 students. Sampling by using purposive sampling with amount as much as 33 student. Result of research: parent support to menstruation enter enough category as much 47,2% of respondents. Students' knowledge about menstruation is categorized as good as 66.7% of respondents. While the readiness of students in the face of menstruation is said to be as much as 88.9%. The value of p value on pearson correlation test between parental support and side readiness is 0,011 where p value <0,05 meaning there is significant relation between parent support with readiness of student in facing menstruation. While the value of p value of Pearson correlation test between students 'knowledge with the readiness offemale students in facing menstruation is 0.001 where p value <0.05 which means there is a relationship between students' knowledge about menstruation and readiness of students in the face of menstruation. Conclusion: There is a relationship between the support of parents and the knowledge of female students with the readiness of female students in facing menstruation in MI sanggrong, tegalrejo, purwantoro, wonogiri with p value 0.001 and 0.011